1996
DOI: 10.4049/jimmunol.157.9.4173
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of IL-12 on allergic lung inflammation depend on timing of doses.

Abstract: We investigated the effects of IL-12 on a murine model of allergic lung inflammation. Administration of IL-12 was timed to interfere with either allergic sensitization (early dosage) or the hypersensitivity inflammatory response in the lung (late dosage), or both (early and late dosages). Comparisons of IL-12- and PBS-treated animals within each treatment group revealed several noticeable effects of IL-12. Early dosage, and the combination of early and late dosages, strikingly decreased ragweed-specific serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The reduction in peripheral blood eosinophilia observed in the present study is consistent with an up-regulation of IL-12 and IFN-g. Sur et al showed that administration of IL-12 decreased allergen-induced lung eosinophilia in a murine model of ragweed allergy [32]. Similar effects were found when as little as 0•1 mg/day was given to D. pteronyssinus-sensitized mice [8].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The reduction in peripheral blood eosinophilia observed in the present study is consistent with an up-regulation of IL-12 and IFN-g. Sur et al showed that administration of IL-12 decreased allergen-induced lung eosinophilia in a murine model of ragweed allergy [32]. Similar effects were found when as little as 0•1 mg/day was given to D. pteronyssinus-sensitized mice [8].…”
Section: Discussionmentioning
confidence: 79%
“…Sur et al . showed that administration of IL‐12 decreased allergen‐induced lung eosinophilia in a murine model of ragweed allergy [32]. Similar effects were found when as little as 0·1 µ g/day was given to D. pteronyssinus ‐sensitized mice [8].…”
Section: Discussionmentioning
confidence: 80%
“…Diversos protocolos de indução da asma têm sido publicados utilizando variados tipos de antígenos, vias de aplicação, doses e tempos de avaliação. Os antígenos aplicados em modelos animais incluem alguns dos quais estão freqüentemente associados com a asma em humanos, tais como pó ou poeira, alimentos e fungos, ao passo que muitos utilizam a ovalbumina (OVA) mesmo com pouca relevância clínica (Yssel et al, 1992;Sur et al, 1996;Lewkowich et al, 2005). O procedimento freqüentemente utilizado em modelos animais é a indução de um estado alérgico, frente ao uso de antígeno conhecido, como a OVA, onde normalmente se empregam 2 injeções deste alergeno associado ao alúmen (hidróxido de alumínio).…”
Section: Modelos De Asma Experimentalunclassified